(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
This paper focuses on the long-term objective of the Firearms Protocol supplementing the United Nations Convention against Transnational Organized Crime to reduce certain kinds of armed violence associated with the misuse of firearms. More than 15 years after the Protocol has come into force, the authors ask how its possible impacts on armed violence might be assessed; indicate key challenges for such an enterprise, and suggest directions for future work in this area, towards the establishment of a measurement tool which could help inform the recently established Review Mechanism of the Protocol.